2022
DOI: 10.3389/fpsyg.2022.890062
|View full text |Cite
|
Sign up to set email alerts
|

How does goal orientation affect employees’ innovation behavior: Data from China

Abstract: The study takes an interaction perspective to examine possible interaction effects of goal orientation, psychological capital, and organizational innovation climate aimed at enhancing employees’ innovation behavior. A total sample of 398 employees were selected in Chinese enterprises. The descriptive statistical analyses, multiple regression, and bootstrap approach are adopted to test the interactive effects after controlling for gender, age, years for work of employees, type of enterprises, and industry. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 95 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…Goal orientation is an intrinsic feature that is highly relevant to work behavior, work attitude, and job performance. For achievement of organizational goals to be actualized, a high level of ability and effort must be put forth by an individual (Zhen, Cao & Wang, 2022). Stasielowicz (2018) argues that examination of goal relevant behaviour should be anchored upon the understanding of underlying commitment mechanisms that motivate individuals to perform.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Goal orientation is an intrinsic feature that is highly relevant to work behavior, work attitude, and job performance. For achievement of organizational goals to be actualized, a high level of ability and effort must be put forth by an individual (Zhen, Cao & Wang, 2022). Stasielowicz (2018) argues that examination of goal relevant behaviour should be anchored upon the understanding of underlying commitment mechanisms that motivate individuals to perform.…”
Section: Introductionmentioning
confidence: 99%
“…According to Akinlabi, Dogo and Asikhia (2021), goals direct individuals' attention toward goal-relevant actions and create a framework for the interpretation of and reaction to related events and outcomes. As one of the pioneer of GO, Carol Dweck was mainly concerned with examining children in a school setting (Zhen et al, 2022). Dweck observed that children with mastery-oriented response patterns responded to failure with solution-oriented selfinstructions, maintained a positive effect, and their subsequent performance on the task improved (Shamin, Cang and Yu, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations